Synthesis of basement membrane-specific macromolecules by cultured human microvascular endothelial cells isolated from skin of diabetic and nondiabetic subjects - Fuh, G.M.; Bensch, K.; Karasek, M.A.; Kramer, R.H. (Microvascular research, 1986)
Microvascular endothelial cells isolated from abdominal skin of diabetic and nondiabetic adults were maintained in culture by serial passage. Both cell types showed typical endothelial cell morphology, expressed factor VIII-associated antigen, contained Weibel-Palade bodies, and produced an extensive subendothelial extracellular matrix containing type IV (basement membrane) procollagen. Biosynthetic studies using radioactive amino acids indicated that under the conditions of cell culture the matrix proteins newly synthesized by MEC of both cell types were similar in type and amount. Both cell types produced type IV procollagen, laminin, and fibronectin, which were deposited in the matrix. Electron microscopy showed that the matrices of both cell types had a similar multilayered, discontinuous, filamentous ultrastructure. Immunoperoxidase staining showed type IV collagen to be distributed similarly, in a fibrillar meshwork, in both matrices. The extractability of individual matrix macromolecules from both matrices was identical; 4 M urea or guanidine-HCl partially removed fibronectin and thrombospondin, but reducing agent was required to solubilize type IV procollagen. The results suggest that diabetic microangiopathy is not due to an inherent defect in the endothelium, and that this in vitro system may be useful for examining environmental factors possibly involved in its development.